Nitrogen Doped Carbon Nanosheets Encapsulated in situ Generated Sulfur Enable High Capacity and Superior Rate Cathode for Li-S Batteries - Guo, Zhijun; Feng, Xiaoyu; Li, Xingxing; Zhang, Xuming; Peng, Xiang; Song, Hao; Fu, Jijiang; Ding, Kang; Huang, Xian; Gao, Biao (Frontiers in Chemistry, 2018)
Lithium-sulfur batteries (Li-S), with large specific capacity (1675 mAh g-1), are regarded as the most likely alternative to the traditional Lithium-ion batteries (LIBs). However, the intrinsical insulation and dramatic volume change of sulfur, as well as serious shuttle effect of polysulfides hinder their practical implementation. Herein, we develop three-dimensional micron flowers assembled by nitrogen doped carbon (NC) nanosheets with sulfur encapsulated (S@NC-NSs) as a promising cathode for Li-S to overcome the forementioned obstacles. The in situ generated S layer adheres to the inner surface of the hollow and micro-porous NC shell with fruitful O/N containing groups endowing both efficient physical trapping and chemical anchoring of polysulfides. Meanwhile, such a novel carbon shell helps to bear dramatic volume change and provides a fast way for electron transfer during cycling. Consequently, the S@NC-NSs demonstrate a high capacity (1238 mAh g-1 at 0.2 C), superior rate performance with a capacity retention of 57.8% when the current density increases 25 times from 0.2 to 5.0 C, as well as outstanding cycling performance with an ultralow capacity fading of only 0.064% after 200 cycles at a high current density of 5.0 C (1.0 C=1675 mAh g-1).